Hermeneutics of Ikat Weaving (Utan) Lian Lipa from Sikka Regency, East Nusa Tenggara (NTT) - Leonard Davinci Elain Koten; Reza Safitri; Maulina Pia Wulandari (GoAcademica Research & Publishing, 2021)
Indonesia is famous for the amazing diversity of woven fabrics, so it has a special place in the hearts of its people. This diversity of woven fabrics is also owned by the people of Sikka Regency, East Nusa Tenggara (NTT) Province. The type of woven fabric that is well-known in the Sikka Regency area is ikat woven fabric (Tallo, 2003). In general, the ikat woven fabrics of Sikka Regency can be distinguished based on gender, namely the women's woven ikat cloth which in Sikka-Krowe language is called utan and the male woven ikat cloth called ragi or lipa. One of the women's ikat cloth (utan) originating from Sikka Regency, namely the Lian Lipa utan. However, the existence of the Lian Lipa utan is still unknown to some people in Sikka Regency, especially related to symbols, such as the motifs on the woven cloth. Apart from symbols, other factors such as norms, social status, traditions and community beliefs attached to this forest are also not widely known. Thus, an in-depth study is needed to be able to answer the overall symbolic meaning of the Lian Lipa utan, namely through a hermeneutic phenomenological approach. Thus, this study aims to determine the hermeneutics of the woven ikat (utan) Lian Lipa. The research methodology used is a qualitative method and the data collection techniques are observation, in-depth interviews and document studies. Through a hermeneutic phenomenological approach by using the Symbolic Interaction Theory of George Herbert Mead and Herbert Blumer, the results of his research show that the hermeneutics of the ikat cloth motif basically comes from the mindset and process of social interaction that has taken place since ancient times.